2003
DOI: 10.1161/01.res.0000105570.34585.f2
|View full text |Cite
|
Sign up to set email alerts
|

Mnk1 Is Required for Angiotensin II–Induced Protein Synthesis in Vascular Smooth Muscle Cells

Abstract: Abstract-Angiotensin II (Ang II) stimulates protein synthesis in vascular smooth muscle cells (VSMCs), possibly secondary to regulatory changes at the initiation of mRNA translation. Mitogen-activated protein (MAP) kinase signal-integrating kinase-1 (Mnk1), a substrate of ERK and p38 MAP kinase, phosphorylates eukaryotic initiation factor 4E (eIF4E), an important factor in translation. (VSMCs) and may contribute to pathological states associated with atherosclerosis, hypertension, and balloon injury. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
24
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 27 publications
5
24
0
Order By: Relevance
“…We previously demonstrated that Ras is required for activation of Mnk1/2, which are kinases that are downstream of extracellular signal-regulated kinase (ERK) (22). To determine the role of ERK1/2 and other MAP kinase family members in Ang II-induced OPN expression, pharmacological inhibitors and kinase-inactive mutants of MEK1 (the kinase immediately upstream kinase of ERK), JNK, and p38MAPK were used.…”
Section: Erk Mediates Ang Ii-induced Opn Transcriptionmentioning
confidence: 99%
“…We previously demonstrated that Ras is required for activation of Mnk1/2, which are kinases that are downstream of extracellular signal-regulated kinase (ERK) (22). To determine the role of ERK1/2 and other MAP kinase family members in Ang II-induced OPN expression, pharmacological inhibitors and kinase-inactive mutants of MEK1 (the kinase immediately upstream kinase of ERK), JNK, and p38MAPK were used.…”
Section: Erk Mediates Ang Ii-induced Opn Transcriptionmentioning
confidence: 99%
“…In reviewing the literature on such cytosolic substrates of ERK1/2, we found a number of proteins involved in the modulation of protein synthesis, including MAP kinase-interacting kinase 1 (Mnk1). Because Mnk1 can be activated by a 7TMR (11), the angiotensin II receptor, we reasoned it might well be a ␤-arrestin ERK1/2 substrate and that ␤-arrestins might be involved in signaling to protein synthesis.…”
mentioning
confidence: 99%
“…Using rat vascular smooth muscle cells, Ishida et al (19) measured the protein synthetic response to angiotensin II (AngII) (11). By using a chemical inhibitor of Mnk1 kinase activity, the authors found that Mnk1 activity was absolutely required for AngII stimulation of protein synthesis.…”
mentioning
confidence: 99%
“…In vascular smooth muscle cells, the activation of Mnk1/eIF4E pathway contributes to Ang II-induced protein synthesis and hypertrophy. 35 One recent research demonstrated that Mnk inhibitor CGP57380 affected translation of only those mRNAs that contain both a cap and a hairpin in the 5′-untranslated regions. 36 Mnk1 may affect translation of specific mRNAs in different cells.…”
Section: Discussionmentioning
confidence: 99%